PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK MUTUAL STORYTELLING UNTUK MEREDUKSI KECEMASAN KORBAN BULLYING - Risya Maulidinda; Raudah Zaimah Dalimunthe; Bangun Yoga Wibowo (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2021)
The purpose of this study was to give the effect of the mutual storytelling technique group guidance services to reduce the anxiety of victims of bullying in class VIII students at SMP Negeri 5 Cilegon City. This study is a quantitative study using a pre-experimental method of one group pre-test and post-test design, with a population of 252 class VIII students and the research sample was taken by purposive sampling technique, namely 6 students who have high anxiety due to bullying behavior. The research data analysis technique uses the Wilcoxon hypothesis test, with an average decrease of 3.50 and a sum of ranks of 21.00, and it is known that Asymp. Sig (2-tailed) is worth 0.028 which is smaller than <0.05. From the results of these calculations, it can be stated that there is an effect of using mutual storytelling technique group guidance in reducing the anxiety of bullying victims in students.